2013
DOI: 10.5430/jnep.v3n8p41
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of drug related problems by home healthcare employees: A Dutch observational study with self reports

Abstract: Background: In the Netherlands, the majority (80%) of the older people (age>65) do use prescribed drugs. 82% of the patients who receive home healthcare are 65 years of age or older. Because of natural changes in age-related drug metabolism, these older home healthcare patients are particularly vulnerable to drug-related problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…nonadherence) by using a recently developed instrument (Additional file 2 . Adapted Red Flag instrument) based on the Red Flag instrument by Sino et al [ 31 ] The observed problems are documented by the CCRN in the Adapted Red Flag instrument and evaluated by the pharmacist-investigator who has identified DRP and proposed suitable solutions. Subsequently the CCRN discusses these DRP and proposed solutions with the responsible healthcare providers.…”
Section: Methodsmentioning
confidence: 99%
“…nonadherence) by using a recently developed instrument (Additional file 2 . Adapted Red Flag instrument) based on the Red Flag instrument by Sino et al [ 31 ] The observed problems are documented by the CCRN in the Adapted Red Flag instrument and evaluated by the pharmacist-investigator who has identified DRP and proposed suitable solutions. Subsequently the CCRN discusses these DRP and proposed solutions with the responsible healthcare providers.…”
Section: Methodsmentioning
confidence: 99%
“…Det är alltså inte bara att köpa in teknisk utrustning och tro att det sedan fungerar, utan vården kan behöva anpassas och personal utveckla sin digitala kompetens [37]. Läkemedelsbehandling är dessutom en av sjuksköterskornas sedvanliga uppgifter, inte minst eftersom de anses ha en god förmåga och kunskap att identifiera läkemedelsavvikelser [42].…”
Section: Analysunclassified